Self-regulation of pharmaceutical activity in Ukraine: opinion of pharmacists and pharmacy technicians - B. Р. Hromovyk (Фармацевтичний журнал, 2020)
The Sustainable Development Goals for 2016–2030, approved in September 2015 at the United Nations Summit, are possible only if the institution of self-regulation of pharmaceutical activities (SRFD) is built and further effective cooperation of public authorities with self-regulatory pharmaceutical organizations (SRPhO). The results of the study of sources of scientific literature show that various aspects of the formation of SRPhA in Ukraine have been studied by a number of domestic researchers. Despite this, a number of little-studied and debatable issues remain that require further research.